PKM USAHA PANGAN LOKAL PEMBUATAN OPAK UBI RASA MANIS - Zaldy Kurniawan Zaldy; Ilham Ary Wahyudie (Jurnal Pengabdian Masyarakat Polmanbabel, 2023)
In line with the increasing market demand, some cassava is cultivated in Indonesia. As a food ingredient, cassava has advantages compared to other food ingredients. One of the growing home industries that produces snacks in the form of cassava-based opaque. The survey was conducted at PKM for the manufacture of sweet potato opaque with cassava-based ingredients produced by the home industry "Opak AS" which is located at Jalan Bukit Ubi, Air Kenanga Environment in Sungailiat District, with the ability to process 20 kg of opaque for 5 hours manually. Using hands, so the results are less efficient and not optimal because it requires a lot of effort and time. In addition, innovation is needed to increase production capabilities. Therefore, a suitable technical machine is needed which is capable of printing opaque with the same diameter and thicknessFrom this problem, to achieve this goal as a servant of the Educational Institution will provide a solution by providing an appropriate technology machine to print opaque with a diameter of 60mm and a thickness of 2mm with a production capacity of 30kg/hour. Thus, it can help the process of production, marketing and machine maintenance independently. After that, evaluation and monitoring is carried out to partners so that the level of success of the partner's production process problems can be measured. The output target resulting from this community service is media publications, cassava opak printing machines can increase the output time of cassava opak production by more than 100%. From the test results it can print 30 kilograms of opaque dough in 1 hour. After using the printing machine the uniformity of the shape and thickness of the opaque is getting better by 94%.